AgCl-RuO2-Co3O4 / SiO2 electrocatalyst as well as preparation method and application thereof
By loading the electrocatalysts of AgCl, RuO2 and Co3O4 nanoparticles on mesoporous SiO2 material, the problems of low activity and high overpotential of existing OER electrocatalysts are solved, and efficient and stable acidic electrocatalytic oxygen evolution performance are achieved.
Patent Information
- Application Number
- CN202411580256.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-11-07
AI Technical Summary
The existing OER electrocatalysts have problems such as low activity and high overpotentials, and Ru is extremely scarce as a precious metal, resulting in its further promotion and application being limited.
AgCl-RuO2-Co3O4/SiO2 electrocatalyst and mesoporous SiO2 material are used as support, and AgCl, RuO2 and Co3O4 nanoparticles are supported. The specific surface area and metal active sites of the catalyst are prepared by combining impregnation and calcination.
The rate and stability of the OER reaction are significantly improved, and the oxygen evolution overpotential is reduced to 20mV@10mA·cm-2, which has excellent acidic electrocatalytic oxygen evolution performance, reduces power consumption, and improves the utilization rate of the catalyst.
Smart Images

Figure CN119433603A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrocatalytic oxygen evolution, and in particular to an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst and a preparation method and application thereof. Background Art
[0002] The electrocatalytic oxygen evolution reaction (OER) is a key electrochemical reaction process of oxygen evolution reaction at zinc electrodeposition anode. However, in the OER electron transfer process, multiple electron transfer will lead to high overpotential, so that the whole reaction shows a slow rate. Therefore, it is necessary to develop efficient and stable OER electrocatalysts to increase the reaction rate to meet the requirements of practical applications.
[0003] At present, ruthenium (Ru)-based OER electrocatalysts have become mainstream electrocatalysts due to their excellent activity and excellent stability, but existing OER electrocatalysts have problems such as low activity and high overpotential. In addition, Ru as a precious metal is extremely scarce, and the further promotion and application of Ru-based OER electrocatalysts are also severely restricted by the reserves and high cost of Ru itself. Therefore, it is extremely important to develop a new OER electrocatalyst system. Summary of the invention
[0004] In view of the above-mentioned deficiencies in the prior art, the object of the present invention is to provide a AgCl-RuO2-Co3O4 / SiO2 electrocatalyst and a preparation method and application thereof, aiming to solve the problems of low activity and high overpotential of existing OER electrocatalysts.
[0005] The technical solution of the present invention is as follows:
[0006] In a first aspect of the present invention, there is provided an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst, which comprises a mesoporous SiO2 material, and AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles supported on the mesoporous SiO2 material.
[0007] Optionally, the mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is (1-3):(1.5-2.5):(2.5-3.5):(2-4).
[0008] The second aspect of the present invention provides a method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst of the present invention, which comprises the steps of:
[0009] S1. Providing mesoporous SiO2 material;
[0010] S2. The mesoporous SiO2 material is prepared into a first solution, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are prepared into a second solution, the first solution and the second solution are mixed, and the mixture is impregnated, dried and calcined to obtain an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst.
[0011] Optionally, the mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is (1-3):(1.5-2.5):(2.5-3.5):(2-4).
[0012] Optionally, the immersion temperature is 35 to 45° C., and the immersion time is 18 to 24 hours.
[0013] Optionally, the drying temperature is 120-150° C., and the drying time is 8-12 hours.
[0014] Optionally, the calcination temperature is 450-500° C., and the calcination time is 5-8 hours.
[0015] Optionally, the step of preparing the mesoporous SiO2 material into a first solution specifically includes:
[0016] The mesoporous SiO2 material is dispersed in water to prepare a first solution, wherein the mass ratio of the mesoporous SiO2 material to water is 1 mg: (10-40) g.
[0017] Optionally, the step of preparing the second solution with AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles specifically includes:
[0018] AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are dispersed in water to prepare a second solution, wherein the mass ratio of the total mass of the AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles to water is 1 mg:(20-60) g.
[0019] The third aspect of the present invention provides an application of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst of the present invention in an electrocatalytic oxygen evolution reaction in an acidic environment.
[0020] Beneficial effects: The present invention provides an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst, which uses mesoporous SiO2 material as a carrier and has a nano-mesoporous structure, thereby ensuring a larger specific surface area of the catalyst, which is beneficial to increasing the metal active sites of the catalyst. At the same time, it is loaded with AgCl, RuO2 and Co3O4 nanoparticles, and the catalytic particles are evenly distributed, and the catalytic activity is strong. The oxygen evolution overpotential of the electrocatalyst is as low as 20mV@10mA·cm -2 , having excellent acidic electrocatalytic oxygen evolution performance. The present invention also successfully prepares the electrocatalyst by combining impregnation and calcination, which is simple, efficient, low-cost, and has the advantages of controllable preparation, and is suitable for industrial production and large-scale application. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is the SEM image of the mesoporous SiO2 material prepared in Example 1.
[0022] Figure 2 This is the SEM image of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1.
[0023] Figure 3 This is the XRD pattern of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1.
[0024] Figure 4 This is the XPS graph of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1.
[0025] Figure 5 The current density-voltage curves of the electrocatalyst prepared in Example 1, the electrocatalyst prepared in Comparative Examples 1 to 3, and the working electrode made of commercially available RuO2 electrocatalyst.
[0026] Figure 6 This is a chronopotentiometric curve of the working electrode made of the electrocatalyst prepared in Example 1. DETAILED DESCRIPTION
[0027] The present invention provides a AgCl-RuO2-Co3O4 / SiO2 electrocatalyst and a preparation method and application thereof. To make the purpose, technical solution and effect of the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0028] An embodiment of the present invention provides an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst, which includes a mesoporous SiO2 material, and AgCl nanoparticles, RuO2 nanoparticles, and Co3O4 nanoparticles supported on the mesoporous SiO2 material.
[0029] The AgCl-RuO2-Co3O4 / SiO2 electrocatalyst in the embodiment of the present invention uses mesoporous SiO2 material as a carrier, has a nano-mesoporous structure, and is loaded with AgCl, RuO2 and Co3O4 nanoparticles with catalytic performance. The catalytic particles are evenly distributed, the catalytic activity is strong, and it has excellent acidic electrocatalytic oxygen evolution performance. On the one hand, the mesoporous SiO2 material has a unique pore structure, which ensures a large specific surface area of the catalyst, is conducive to increasing the metal active sites of the catalyst, and improving the utilization rate of the precious metal Ru and other catalytic elements. At the same time, it is also conducive to the flow of electrolyte and the escape of oxygen in the OER reaction, and improves the catalytic activity of the electrocatalyst; on the other hand, the catalytic synergistic effect of AgCl, RuO2 and Co3O4 nanoparticles can accelerate the precipitation of oxygen, so that the overpotential of the OER reaction is reduced, thereby effectively reducing power consumption and further improving the catalytic activity of the electrocatalyst. In addition, compared with existing OER electrocatalysts, the present invention reduces the amount of RuO2 used by introducing AgCl and Co3O4 on the mesoporous SiO2 material, and jointly regulates the catalyst performance with RuO2, which can greatly improve the utilization rate of the catalytic element. Compared with commercial pure RuO2 catalysts, it is cheaper and has good application prospects.
[0030] The AgCl-RuO2-Co3O4 / SiO2 electrocatalyst in the embodiment of the present invention has a nano-mesoporous structure of a mesoporous SiO2 material, and AgCl, RuO2 and Co3O4 nanoparticles are evenly distributed inside and outside the mesoporous SiO2 material, so that the metal elements can be maximized. The AgCl-RuO2-Co3O4 / SiO2 electrocatalyst has excellent acidic electrocatalytic oxygen evolution performance and can be used at 10 mA cm -2 The current density remains stable for more than 78 hours, and the oxygen evolution overpotential is lower than that of commercial RuO2. -2 Only 20mV is required at a current density of 1.5V.
[0031] In some embodiments, the mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is (1-3):(1.5-2.5):(2.5-3.5):(2-4).
[0032] In this embodiment, the mass ratio of the three catalytic particles (AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles) to the carrier (mesoporous SiO2 material) is mainly determined based on their own catalytic effects and the synergistic effect between the various catalytic particles. The catalyst prepared within the mass ratio range has the best catalytic effect and the oxygen evolution overpotential can reach the lowest.
[0033] An embodiment of the present invention provides a method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst described in any of the above embodiments, comprising the steps of:
[0034] S1. Providing mesoporous SiO2 material;
[0035] S2. The mesoporous SiO2 material is prepared into a first solution, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are prepared into a second solution, the first solution and the second solution are mixed, and the mixture is impregnated, dried and calcined to obtain an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst.
[0036] The embodiment of the present invention successfully prepares the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst by a method combining impregnation and calcination. First, the mesoporous SiO2 material and the AgCl, RuO2, and Co3O4 nanoparticles are dispersed in the liquid phase and then mixed. Subsequently, the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst can be obtained by impregnation and high-temperature calcination. The method provided by the embodiment of the present invention is simple, efficient, low-cost, and has the advantages of controllable preparation, which is suitable for industrial production and large-scale application. The electrocatalyst finally prepared also has the nano-mesoporous structure of the mesoporous SiO2 material, and the AgCl, RuO2, and Co3O4 nanoparticles with catalytic performance are evenly distributed, have strong catalytic activity, and have excellent acidic electrocatalytic oxygen evolution performance.
[0037] In step S1, in some embodiments, the mesoporous SiO2 material can be directly purchased or prepared by conventional methods in the art, which is not limited here.
[0038] In some preferred embodiments, the method for preparing the mesoporous SiO2 material comprises the steps of:
[0039] Pluronic F127, water and hydrochloric acid are mixed and stirred to obtain a transparent solution, and n-butanol and ethyl orthosilicate are then added and stirred, and a mesoporous SiO2 material is obtained through a hydrothermal reaction.
[0040] In this embodiment, the surfactant Pluronic F127, water and hydrochloric acid are first mixed and stirred to obtain a transparent solution, and then n-butanol and tetraethyl orthosilicate are added in sequence and mixed and stirred, and then a mesoporous SiO2 material is obtained through a hydrothermal reaction. The prepared mesoporous SiO2 material is small in size and has a unique pore structure, which ensures a large specific surface area of the catalyst and is beneficial to increase the metal active sites of the catalyst.
[0041] In this embodiment, Pluronic F127, also known as Poloxamer F127, is a nonionic surfactant belonging to the Pluronic polymer family. Pluronic F127 is composed of blocks of two different polymers, polyoxyethylene (PEO) and polyoxypropylene (PPO), and has a triblock structure, usually represented as PEO-PPO-PEO.
[0042] In this embodiment, the mass ratio of Pluronic F127, water and hydrochloric acid is (1-5):(100-150):(10-25). Within this mass ratio range, a mesoporous SiO2 material with a pore microstructure can be successfully prepared.
[0043] In this embodiment, the concentration of the hydrochloric acid is 36% to 38%, wherein the concentration of the hydrochloric acid is a mass percentage concentration.
[0044] In this embodiment, the volume ratio of n-butanol to tetraethyl orthosilicate is (8-13):(10-20). Within this volume ratio range, SiO2 material with a pore microstructure can be successfully prepared.
[0045] In this embodiment, the reaction temperature of the hydrothermal reaction is 120-150° C., and the reaction time is 20-24 hours. Within the reaction temperature and time range, the material can be fully aged, so that the particle size of the SiO2 material after calcination is smaller.
[0046] In some embodiments, the step of mixing Pluronic F127, water and hydrochloric acid to obtain a transparent solution, adding n-butanol and ethyl orthosilicate, mixing and stirring, and obtaining the mesoporous SiO2 material through a hydrothermal reaction specifically includes:
[0047] Pluronic F127, water and hydrochloric acid are mixed and stirred at room temperature for 1 to 2 hours to obtain a transparent solution, n-butanol is added and stirred at room temperature for 0.5 to 1 hour, and then ethyl orthosilicate is added and stirred at 38 to 42°C for 22 to 26 hours to obtain a mesoporous SiO2 material through a hydrothermal reaction.
[0048] In step S2, in some embodiments, the mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is (1-3): (1.5-2.5): (2.5-3.5): (2-4). Within this mass ratio range, the three catalytic particles can be fully mixed with the mesoporous SiO2 material, and the synergistic effect between the catalytic particles is optimal, so that the catalytic effect of the catalyst is optimal.
[0049] In some preferred embodiments, the mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is 2:2:3:3.
[0050] In some embodiments, the impregnation temperature is 35 to 45° C., and the impregnation time is 18 to 24 hours. The present invention uniformly loads AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles on the mesoporous SiO2 material by an impregnation method. Within the impregnation temperature and time range, the three catalytic particles can be uniformly dispersed inside and outside the SiO2 material, so that the catalytic metal elements are maximized.
[0051] In some embodiments, the drying temperature is 120-150° C., and the drying time is 8-12 hours. The purpose of the drying is to collect the powder material. Within the drying temperature and time range, the moisture inside and outside the material can be effectively dried, and the material is fully ground to obtain a powder material.
[0052] In some embodiments, the calcination temperature is 450-500°C, the calcination time is 5h-8h, and the calcination heating rate is 5-10°C / min. The purpose of the calcination is to remove the organic mesoporous SiO2 material. Within the calcination temperature and time range, the mesoporous SiO2 material can effectively carry out the combustion reaction, and the catalyst after calcination is effectively freed of organic matter, but the pore microstructure of the mesoporous SiO2 is still retained.
[0053] In some embodiments, the step of preparing the mesoporous SiO2 material into a first solution specifically includes:
[0054] The mesoporous SiO2 material is dispersed in water (preferably distilled water) to prepare a first solution, wherein the mass ratio of the mesoporous SiO2 material to water is 1 mg: (10-40) g.
[0055] In some preferred embodiments, the mass ratio of the mesoporous SiO2 material to water is 1 mg:20 g.
[0056] In some embodiments, the step of preparing the second solution with AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles specifically includes:
[0057] AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are dispersed in water (preferably distilled water) to prepare a second solution, wherein the mass ratio of the total mass of AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles to water is 1 mg: (20-60) g.
[0058] In some preferred embodiments, the mass ratio of the total mass of the AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles to water is 1 mg:40 g.
[0059] An embodiment of the present invention provides an application of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst described in any of the aforementioned embodiments in an electrocatalytic oxygen evolution reaction in an acidic environment.
[0060] The AgCl-RuO2-Co3O4 / SiO2 electrocatalyst in the embodiment of the present invention has excellent acidic electrocatalytic oxygen evolution performance and can be used at 10 mA cm -2 The current density remains stable for more than 78 hours, and the oxygen evolution overpotential is lower than that of commercial RuO2. -2 Only 20mV is required at a current density of 1.5V.
[0061] The present invention will be further described below by means of specific examples.
[0062] Example 1
[0063] This embodiment provides a method for preparing a AgCl-RuO2-Co3O4 / SiO2 electrocatalyst, which is as follows:
[0064] (1) 3.0 g of Pluronic F127, 144 g of distilled water, and 16.4 g of hydrochloric acid were mixed at room temperature and stirred using a magnetic stirrer for 1 h until a transparent solution was formed, 11.0 mL of n-butanol was added as a cosolvent, and stirring was continued for about 0.5 h. Then, 15.3 mL of tetraethyl orthosilicate (TEOS) was added, and the mixture was stirred at 40° C. for 24 h to obtain a mixture.
[0065] (2) The mixture obtained in step (1) was transferred to a 250 mL Teflon-lined reactor, placed in a drying oven at 150° C. for hydrothermal reaction for 24 h, then washed with ethanol and distilled water and filtered, and dried overnight to obtain a mesoporous SiO2 material.
[0066] (3) The mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles obtained in step (2) are weighed respectively according to a mass ratio of 2:2:3:3, 2 mg of the mesoporous SiO2 material is dispersed in distilled water with a solid-liquid ratio of 1 mg:20 g to prepare a mesoporous SiO2 material solution, and 8 mg of the total mass of AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are dispersed in distilled water with a solid-liquid ratio of 1 mg:40 g to prepare an AgCl-RuO2-Co3O4 solution, which is stirred for about 1 hour.
[0067] (4) The AgCl-RuO2-Co3O4 solution obtained in step (3) is mixed into the mesoporous SiO2 material solution, first immersed and stirred at 40°C for 24 hours, then dried at 130°C for 12 hours, and finally calcined at 450°C for 6 hours to obtain the final product AgCl-RuO2-Co3O4 / SiO2 electrocatalyst.
[0068] Comparative Example 1
[0069] This comparative example provides a method for preparing a RuO2-Co3O4 / SiO2 electrocatalyst, which is as follows:
[0070] (1) The mesoporous SiO2 material is prepared by the same steps as steps (1) and (2) in Example 1.
[0071] (2) The prepared mesoporous SiO2 material, RuO2 nanoparticles and Co3O4 nanoparticles were weighed in a mass ratio of 2:5:3, and 2 mg of mesoporous SiO2 material was dispersed in distilled water with a solid-liquid ratio of 1 mg:20 g to prepare a mesoporous SiO2 material solution. A total mass of 8 mg of RuO2 nanoparticles and Co3O4 nanoparticles were dispersed in distilled water with a solid-liquid ratio of 1 mg:40 g to prepare a RuO2-Co3O4 solution, which was stirred for about 1 hour.
[0072] (3) The RuO2-Co3O4 solution obtained in step (2) is mixed into the mesoporous SiO2 material solution, first immersed and stirred at 40°C for 24 hours, then dried at 130°C for 12 hours, and finally calcined at 450°C for 6 hours to obtain the final product RuO2-Co3O4 / SiO2 electrocatalyst.
[0073] Comparative Example 2
[0074] This comparative example provides a method for preparing a RuO2 / SiO2 electrocatalyst, which is as follows:
[0075] (1) The mesoporous SiO2 material is prepared by the same steps as steps (1) and (2) in Example 1.
[0076] (2) The prepared mesoporous SiO2 material and RuO2 nanoparticles were weighed separately in a mass ratio of 2:8, 2 mg of mesoporous SiO2 material was dispersed in distilled water with a solid-liquid ratio of 1 mg:20 g to prepare a mesoporous SiO2 material solution, and 8 mg of RuO2 was dispersed in distilled water with a solid-liquid ratio of 1 mg:40 g to prepare a RuO2 solution, which was stirred for about 1 hour.
[0077] (3) The RuO2 solution obtained in step (2) is mixed into the mesoporous SiO2 material solution, first immersed and stirred at 40°C for 24 hours, then dried at 130°C for 12 hours, and finally calcined at 450°C for 6 hours to obtain the final product RuO2 / SiO2 electrocatalyst.
[0078] Comparative Example 3
[0079] This comparative example provides a method for preparing a RuO2-Co3O4 electrocatalyst, which is as follows:
[0080] (1) Weigh 5 mg of RuO2 nanoparticles and 3 mg of Co3O4 nanoparticles, respectively, with a mass ratio of 5:3, and add them into distilled water at a solid-liquid ratio of 1 mg:40 g to prepare a RuO2-Co3O4 solution.
[0081] (3) The RuO2-Co3O4 solution obtained in step (1) was immersed and stirred at 40°C for 24 hours, then dried at 130°C for 12 hours, and finally calcined at 450°C for 6 hours to obtain the final product RuO2-Co3O4 electrocatalyst.
[0082] The following microstructure and morphology tests were performed on the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1, and the OER (oxygen evolution reaction) performance characterization was performed on the electrocatalysts prepared in Example 1, Comparative Examples 1 to 3, and a commercially available RuO2 electrocatalyst (Shanghai MacLean Biotech Co., Ltd., CAS No. 12036-10-1).
[0083] 1. The AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1 was tested for its microstructure and morphology using an X-ray diffractometer and a field emission scanning electron microscope.
[0084] Figure 1 3 is a scanning electron microscope (SEM) image of the mesoporous SiO2 material prepared in Example 1. It can be seen from the image that the mesoporous SiO2 material has a uniformly distributed pore structure.
[0085] Figure 2This is the SEM image of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1. According to the figure, the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1 is relatively uniform, has good crystallinity, and retains the pore microstructure of the carrier mesoporous SiO2 material.
[0086] Figure 3 This is the X-ray diffraction (XRD) pattern of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1. Strong and broad diffraction peaks of AgCl, RuO2 and Co3O4 appear in the pattern, which indicates that the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1 has good crystallinity and small particle size.
[0087] Figure 4 The X-ray photoelectron spectroscopy (XPS) diagram of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1 shows the chemical composition of AgCl, RuO2 and Co3O4. It can be seen that Ag exists in the +1 chemical valence state, Ru and Co exist only in the form of oxides, most of ruthenium exists in the +4 chemical valence state, and Co 2p 3 / 2 and Co 2p 1 / 2 The spin states of Co are indexed at 781.2 eV and 796.5 eV, respectively, indicating that the Co element exists in two chemical valence states of +2 and +3.
[0088] 2. The OER performance of the electrocatalysts prepared in Example 1 and Comparative Examples 1 to 3, as well as the commercially available RuO2 electrocatalysts, was characterized as follows:
[0089] The electrocatalysts prepared in Example 1 and Comparative Examples 1 to 3, as well as commercially available RuO2 electrocatalysts, were made into corresponding working electrodes:
[0090] (1) Weigh 10 mg of the electrocatalyst prepared in Example 1, the electrocatalyst prepared in Comparative Examples 1 to 3, and the commercially available RuO2 electrocatalyst respectively and place them in different 1 mL centrifuge tubes, use a pipette to transfer 100 uL of ethanol, 50 uL of 5 wt.% Nafion solution and 50 uL of isopropanol respectively, and then ultrasonicate for 1 hour to form a uniformly dispersed suspension, wherein the electrocatalyst prepared in Example 1 is made into suspension L1, the electrocatalysts prepared in Comparative Examples 1 to 3 are made into suspensions L2, L3 and L4, respectively, and the commercially available RuO2 electrocatalyst is made into suspension L5.
[0091] (2) The surfaces of five glassy carbon electrodes (surface area 0.196 cm) were treated with anhydrous ethanol and distilled water. 2) for ultrasonic treatment, and then dry naturally for standby use. Then, 5uL of the above suspension L1, suspension L2, suspension L3, suspension L4 and suspension L5 were respectively transferred and added to the corresponding glassy carbon electrode surface in three times, and dried naturally to obtain five working electrodes, among which the electrocatalyst prepared in Example 1 was made into working electrode WE1, the electrocatalysts prepared in Comparative Examples 1 to 3 were made into working electrodes WE2, working electrodes WE3 and working electrodes WE4, and the commercially available RuO2 electrocatalyst was made into working electrode WE5.
[0092] OER performance characterization test method: using a standard three-electrode system at 1 mol·L -1 The electrochemical OER performance test was carried out in H2SO4 solution, and the working electrodes WE1, WE2, WE3, WE4 and WE5 obtained above were used as working electrodes, the counter electrode was a platinum electrode, and the reference electrode was a saturated mercurous sulfate electrode. The polarization curve was tested using linear cyclic voltammetry (LSV), and the test conditions were: the scanning voltage range was -0.5 to 1.5 V (vs. SCE), the scanning rate was 0.01 V / s, and all LSV test data were not compensated for iR (Internal Resistance).
[0093] Test results: Figure 5 The current density-voltage curves of the working electrodes made of the electrocatalyst prepared in Example 1, the electrocatalyst prepared in Comparative Examples 1 to 3, and the commercially available RuO2 electrocatalyst are shown in Table 1. The oxygen evolution overpotentials of the electrocatalyst prepared in Example 1, the electrocatalyst prepared in Comparative Examples 1 to 3, and the commercially available RuO2 electrocatalyst are shown in Table 1. Figure 6 This is a chronopotentiometric curve of the working electrode made of the electrocatalyst prepared in Example 1.
[0094] Table 1 Oxygen evolution overpotential of different electrocatalysts
[0095]
[0096]
[0097] According to Table 1, Figure 5 and Figure 6 It can be seen that the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1 of the present invention has a high conductivity at 10 mA·cm -2At a current density of 1.5 Å, the oxygen evolution overpotential is only 20 mV, which is about 200 mV lower than that of the commercial RuO2 electrocatalyst and is also much lower than that of the other electrocatalysts in Comparative Examples 1 to 3. In addition, during the chronopotentiometry test, the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst prepared in Example 1 can maintain a stable potential for more than 78 h @ 10 mA cm -2 These data indicate that the electrocatalytic oxygen evolution performance of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst of the present invention in an acidic environment is higher than that of RuO2-Co3O4 / SiO2, RuO2 / SiO2, RuO2-Co3O4 and commercially available RuO2 electrocatalysts, wherein there is a synergistic effect between the AgCl, RuO2 and Co3O4 nanoparticles, and the introduction of the carrier mesoporous SiO2 material can improve the utilization of the precious metal Ru and other catalytic elements, accelerate the precipitation of O2, greatly reduce the overpotential of the OER reaction, and significantly improve the catalyst activity.
[0098] In summary, the present invention provides an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst, which uses a mesoporous SiO2 material as a carrier and is loaded with AgCl, RuO2 and Co3O4 nanoparticles. On the one hand, the mesoporous SiO2 material has a unique pore structure, which ensures a large specific surface area of the catalyst, is beneficial to increase the metal active sites of the catalyst, improves the utilization rate of the precious metal Ru and other catalytic elements, and is also beneficial to the flow of electrolyte and the escape of oxygen in the OER reaction, thereby improving the catalytic activity of the electrocatalyst; on the other hand, the catalytic synergistic effect of the AgCl, RuO2 and Co3O4 nanoparticles can accelerate the precipitation of oxygen, reduce the overpotential of the OER reaction, thereby effectively reducing power consumption and further improving the catalytic activity of the electrocatalyst.
[0099] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.
Claims
1. An AgCl-RuO2-Co3O4 / SiO2 electrocatalyst, characterized in that: The invention comprises a mesoporous SiO2 material, and AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles loaded on the mesoporous SiO2 material.
2. The AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 1, characterized in that The mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is (1-3):(1.5-2.5):(2.5-3.5):(2-4).
3. A method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst as claimed in claim 1 or 2, characterized in that: Includes steps: S1. Providing mesoporous SiO2 material; S2. The mesoporous SiO2 material is prepared into a first solution, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are prepared into a second solution, the first solution and the second solution are mixed, and the mixture is impregnated, dried and calcined to obtain an AgCl-RuO2-Co3O4 / SiO2 electrocatalyst.
4. The method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 3, characterized in that: The mass ratio of the mesoporous SiO2 material, AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles is (1-3):(1.5-2.5):(2.5-3.5):(2-4).
5. The method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 3, characterized in that: The immersion temperature is 35-45° C., and the immersion time is 18-24 hours.
6. The method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 3, characterized in that: The drying temperature is 120-150° C., and the drying time is 8-12 hours.
7. The method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 3, characterized in that: The calcination temperature is 450-500° C., and the calcination time is 5-8 hours.
8. The method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 3, characterized in that: The step of preparing the mesoporous SiO2 material into a first solution specifically comprises: The mesoporous SiO2 material is dispersed in water to prepare a first solution, wherein the mass ratio of the mesoporous SiO2 material to water is 1 mg: (10-40) g.
9. The method for preparing the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst according to claim 3, characterized in that: The step of preparing the second solution of AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles specifically comprises: AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles are dispersed in water to prepare a second solution, wherein the mass ratio of the total mass of the AgCl nanoparticles, RuO2 nanoparticles and Co3O4 nanoparticles to water is 1 mg:(20-60) g.
10. Use of the AgCl-RuO2-Co3O4 / SiO2 electrocatalyst as claimed in claim 1 or 2 in electrocatalytic oxygen evolution reaction in an acidic environment.
Citation Information
Patent Citations
Heterojunction catalyst for electrocatalytic oxygen evolution reaction under high current density and preparation method thereof
CN117926323A
Meso-porous material containing nano silver granulates and preparing method
CN1978100A